TEACHER COMPETENCE, LEARNING MEDIA, AND MOTIVATION IN RELATION TO ELEMENTARY SCHOOL EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Firman Maulana; Rohimat; Elis Masridah; Ai Nurhaeti; Ade Tutty Rokhayati Rosa (Jurnal Cakrawala Pendas, 2026)
Improving learning outcomes in elementary education requires a comprehensive understanding of multiple educational factors that contribute to effective teaching and learning. This study aims to systematically synthesize empirical evidence regarding teacher competence, instructional media, and learning motivation in relation to elementary school students’ learning outcomes through a Systematic Literature Review (SLR). The review followed the PRISMA 2020 guidelines, encompassing the stages of identification, screening, eligibility assessment, and inclusion. Literature was retrieved from Scopus, SINTA, and Google Scholar, yielding 145 records, of which 20 empirical studies published between 2020 and 2025 met the predefined inclusion criteria and were included in the qualitative synthesis. The findings were analyzed using thematic synthesis and organized into four recurring themes: teacher competence, instructional media, learning motivation, and competence–media integration. The synthesis indicates that teacher competence is consistently associated with instructional quality, while interactive instructional media support students’ engagement and conceptual understanding when integrated appropriately into classroom practices. Learning motivation is frequently reported as an important learner-related factor associated with participation, persistence, and academic achievement. However, variations across studies suggest that these relationships are influenced by differences in educational contexts, instructional approaches, and methodological designs. This review contributes by integrating fragmented empirical evidence into an integrative conceptual framework that organizes recurring research patterns and contextual relationships among the reviewed variables. The findings provide theoretical guidance for future research and practical implications for teacher professional development, instructional innovation, and educational policy aimed at improving elementary school learning outcomes.